AJ Fitness Centre: AJ Wellness Finess Centre / Siti Farhana Abdul Rahim … [et al.] - ABDUL RAHIM, SITI FARHANA; AZMI LEE, LILY SURYANI; ANUAR, NUR SYAZWANI; MOHD ARIFIN, SITI AISYAH; MAT JUSOH, MASITAH (2021)
Entrepreneurship defines as the activity of putting in a business or businesses, taking over monetary risks within the hope of profit (Dorf, Byers, & Nelson, n.d.). The development of entrepreneurship, as each idea and activity, has been growing in importance in Malaysia. The perceived importance of entrepreneurship to the expansion of Malaysia's economy is proved by the sheer quantity and sort of supporting mechanisms and policies that exist for entrepreneurs, together with funding, physical infrastructure, and business informatory services. The establishment of a special ministry for entrepreneurs-the Ministry of entrepreneur Development in 1995, clearly showcases the importance the government places upon the difficulty of entrepreneurship and entrepreneur development (Ariff & Abubakar, n.d.).